An Evaluation of the Photochemical Air Quality Modeling Using Cmaq in the Industrial Area of Quintero-Puchuncavi-Concon, Chile - Diaz-Robles, L (Elsevier B.V., 2022)
The air pollution has impacted for years the population and the ecosystem in the industrial area located in Quintero, Puchuncavi, and Concon counties, the coastal area of Central Chile. In this study, we used the WRF-SMOKE-CMAQ model system to evaluate the photochemical modeling of PM10, PM2.5, and O3. The industrial and the residential wood combustion sources were the main contributors of particulate matter, sulfur dioxide and volatile organic compounds. The small diurnal temperature cycle, the high relative humidity and the low wind speed profiles exposed the meteorological condition of the coastal lows during the period of analysis. The daily average concentrations for PM10 and PM2.5 ranged from 24.03 to 50.10 μg/m3 and 15.60–21.95 μg/m3 for observed registries; meanwhile, the simulated results were in the range of 22.71–40.62 μg/m3 and 5.49–17.29 μg/m3, respectively. The omission of missing sources in the emission inventory and the default values in the boundary condition could be one of the reasons on the underprediction obtained. The best performance for O3 occurred in the Quintero and Sur stations, located near industrial sources with high NOx and VOC emissions. In the industrial complex, PM10 and PM2.5 concentrations were 10–30 μg/m3 lower when the industrial emissions were shut down and a negligible difference was observed when the residential wood combustion emissions were not considered. Future air quality modeling must be performed in the same region for other periods like the Summer season. Also, the emission inventory from all sources needs to be accurate with more accurate temporal profiles. © 2022 Turkish National Committee for Air Pollution Research and Control